Tris(hydroxymethyl)aminomethane and its derivative as organic thermal stabilizers for flexible poly(vinyl chloride). Issue 4 (8th September 2021) - Fu, Zhimin; Yang, Zhanhong; Deng, Lie; Rong, Yao; Wu, Jian
Abstract: The tris(hydroxymethyl)aminomethane (THAM) and its derivative (DHD 2‐([1, 3‐dihydroxypropan‐2‐ylidene]amino)‐2‐(hydroxymethyl)propane‐1, 3‐diol) have been used as organic thermal stabilizers for flexible poly(vinyl chloride) (PVC). According to dehydrochlorination and discoloration tests conducted at 180°C, THAM showed to be an excellent organic thermal stabilizer for flexible PVC, not only THAM stabilizer improved the thermal stability of PVC but also maintained the initial color of the PVC. The induction time and the thermal stability time were 52 and 55.5 min, respectively. DHD can also be used as an organic thermal stabilizer for flexible PVC; however, its thermal stabilizing efficiency was not satisfactory, but it has a good synergistic effect with traditional cadmium–zinc soap stabilizers. Besides, the experiments had been performed to investigate pentaerythritol (PER) and THAM, two substances with similar structure, but such a huge difference in thermal stabilizing efficiency for flexible PVC. THAM did improve the thermal stability of PVC, both in initial whiteness and long‐term thermal stability. But PER has no thermal stabilizing efficiency for PVC when used alone. At the end of the article, the probable mechanism which can give an explanation for the stabilizing efficiency given by the THAM has been proposed. Abstract : Thermal stability mechanism of THAM on PVC. This article introduces a compound of simple structure‐THAM, which can effectively improve the thermal stability of PVC. And a number of experiments have been conducted to investigate a probable mechanism that can give an explanation for the thermal stability given by the THAM.